Democratic State Governance: The Urgency of Implementing Conventions in Constitutional Practices in Indonesia - Muhammad Mutawalli Mukhlis; Paul Atagamen Aidonojie; Zulhilmi Paidi; Muhammad Saleh Tajuddin (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2024)
Constitutional conventions are often used with different meanings depending on the context of the discussion. Constitutional conventions are only limited to agreements between bilateral and multilateral countries, agreements among international law subjects, meetings of political, legislative, fraternal members or representatives, and other organizations. Constitutional conventions are not formed and built from laws, court decisions, or parliamentary customs but are outside of them to regulate political behavior. This research aims to determine the urgency of constitutional practice conventions in Indonesia. This research uses qualitative research. The method used in this research is a normative legal research method. This research concludes that the Convention in constitutional practice in Indonesia has an essential urgency in forming and regulating government governance. The urgency of conventions in constitutional practice is to perfect the constitutional system, empower state institutions, develop constitutional law, and provide crisis resolution in politics.